2022
DOI: 10.1158/0008-5472.can-21-4045
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective Inhibitor JBI-589 Targets PAD4-Mediated Neutrophil Migration to Suppress Tumor Progression

Abstract: Neutrophils are closely involved in the regulation of tumor progression and formation of pre-metastatic niches. However, the mechanisms of their involvement and therapeutic regulation of these processes remain elusive. Here, we report a critical role of neutrophil peptidylarginine deiminase 4 (PAD4) in neutrophil migration in cancer. In several transplantable and genetically engineered mouse models, tumor growth was accompanied by significantly elevated enzymatic activity of neutrophil PAD4. Targeted deletion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…The development of PAD4 inhibitors has continued based on the GSK484 base structure with drugs with oral availability. Compound BMS‐P5 was reported to have efficacy in delaying multiple myeloma progression 234 and the lead candidate JBI‐589 shows efficacy in NET‐mediated sequelae of solid tumors, 235 supporting previous data showing similar protection with PAD4 deficiency in mice 236 . Cancer‐associated thrombosis and metastasis, for which we recently reviewed the implications of NET release, 237,238 indeed represent promising clinical targets for NET inhibition.…”
Section: Net‐targeted Therapiessupporting
confidence: 76%
“…The development of PAD4 inhibitors has continued based on the GSK484 base structure with drugs with oral availability. Compound BMS‐P5 was reported to have efficacy in delaying multiple myeloma progression 234 and the lead candidate JBI‐589 shows efficacy in NET‐mediated sequelae of solid tumors, 235 supporting previous data showing similar protection with PAD4 deficiency in mice 236 . Cancer‐associated thrombosis and metastasis, for which we recently reviewed the implications of NET release, 237,238 indeed represent promising clinical targets for NET inhibition.…”
Section: Net‐targeted Therapiessupporting
confidence: 76%
“…Studies in other systems have shown that various modalities such as PADs inhibitors ( 21 , 36 , 37 ), DNA-degrading DNases ( 4 ), and SNase ( 11 ) can reduce the level of NETs in vivo . Cl-amidine is an effective, small molecular inhibitor of PADs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, however, the decrease in disease severity was less than that observed for BB-Cl-amidine suggesting the possibility that additional isozymes played a role in disease. Several more advanced PAD4 selective inhibitors based on the GSK484 scaffold have been developed including BMS-P5 [53] and JBI-589 (figure 2 c ) [54]. Notably, BMS-P5 efficiently blocks NETosis and improves survival in a murine model of multiple myeloma [53].…”
Section: Selective Protein Arginine Deiminase Inhibitorsmentioning
confidence: 99%